2020
DOI: 10.47613/reflektif.2020.4
|View full text |Cite
|
Sign up to set email alerts
|

Against All Winds: The Populism-Nationalism Nexus in the Rhetoric of the Nationalist Action Party

Abstract: The rise of radical right populist parties in Europe has made it essential for students of political science to understand this amalgam of populism and nationalism.Textbook examples of new actors on the political scene are characterized by a strong populist discourse and a significant nationalist/nativist ideology. The Nationalist Action Party of Turkey ranks high in the list of populist actors (Inglehart & Norris, 2016), and we demonstrate the divergent and convergent points in the populism-nationalism axis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…However, AKP, the party in power since 2002, deepened these divides by utilizing polarizing discourses and continuously pointing out the “foes” of AKP/New Turkey in a simplified frame. Thus, the existing fault lines have been crystallized over the past few years (Erdogan & Uyan-Semerci, 2018; McCoy et al, 2018). Two recent studies on polarization in Turkey funded by the German Marshall Fund show that polarization in Turkey increasingly creates distancing between the supporters of different political parties (Erdogan & Uyan-Semerci, 2018; Erdogan, 2016).…”
Section: Polarization and Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…However, AKP, the party in power since 2002, deepened these divides by utilizing polarizing discourses and continuously pointing out the “foes” of AKP/New Turkey in a simplified frame. Thus, the existing fault lines have been crystallized over the past few years (Erdogan & Uyan-Semerci, 2018; McCoy et al, 2018). Two recent studies on polarization in Turkey funded by the German Marshall Fund show that polarization in Turkey increasingly creates distancing between the supporters of different political parties (Erdogan & Uyan-Semerci, 2018; Erdogan, 2016).…”
Section: Polarization and Social Mediamentioning
confidence: 99%
“…Thus, the existing fault lines have been crystallized over the past few years (Erdogan & Uyan-Semerci, 2018; McCoy et al, 2018). Two recent studies on polarization in Turkey funded by the German Marshall Fund show that polarization in Turkey increasingly creates distancing between the supporters of different political parties (Erdogan & Uyan-Semerci, 2018; Erdogan, 2016). People are very reluctant to discuss contentious political matters in public spaces (e.g., neighborhood meetings) or even at family dinners (Erdogan & Uyan-Semerci, 2018, p. 4).…”
Section: Polarization and Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…However, for so long, the populist democracy narrative of Turkey is based on a context‐dependent but deep‐seated nationalist cleavage: native‐traditional‐religious‐provincial versus nonnative‐modernist‐secularist‐urban. The Manichean populist discourses are created by the distinction between educated‐secular‐modernist‐center and native‐traditional‐periphery (see Mardin, 1973) that has become a long‐lived fertile ground for the “right‐wing populism a la Turca” (Aytaç et al., 2021; Aytaç & Elçi, 2019; Erdoğan & Uyan‐Semerci, 2020a; Elçi, 2019). Populist right‐wing political actors in Turkey such as Adnan Menderes, Süleyman Demirel, Turgut Özal, and Recep Tayyip Erdoğan built their discourses on the dichotomy of secularist state that does not represent “real national values” versus religious and nationalist ordinary people (Çınar & Sayın, 2014; Sözen, 2020).…”
Section: Context‐dependent National Identity Populist Heritage and In...mentioning
confidence: 99%
“…Researchers from Istanbul’s Bilgi University surveyed more than 2,000 Turks regarding their concerns about the refugees in November and December of 2017 and found that three major fears underlie their wish to curb the flow of Syrians into the country: economic fears that scarce resources will dry up, symbolic fears that the cultural values of the country will be compromised by the influence of Arab culture, and fears of physical attack from refugees who are violent (Erdoğan and Semerci, 2018). The authors found that 71.4% of the respondents believe that Syrians take jobs from Turks, 67.4% say that the refugees are the cause of increasing crime rates, and 66.4% worry that moral values and traditions are in danger because of the large numbers of refugees coming into the country.…”
Section: Introductionmentioning
confidence: 99%